Building Information Modeling (BIM) Basic Competency Training to improve Building Construction Service Design Products in Banyumas Regency - Dani Nugroho Saputro; Nor Intang Setyo Hermanto; Gandjar Pamudji; Arnie Widyaningrum; Heryawan Susanto (Universitas Ahmad Dahlan, 2022)
Background: Building Information Modeling (BIM) is a technology in the field of Architecture, Engineering and Construction that is capable of simulating all information in a development project into a three-dimensional (3D) model. One of the government's efforts in dealing with the Industrial Revolution 4.0 is implementing the use of BIM, and construction technology innovations in each project cycle. By applying the BIM method, both managers, consultants and contractors are able to save processing time, costs incurred and the required workforce. The application of BIM technology can minimize the impact of work delays, increased costs, and construction failures. Contribution: The results of the analysis of the needs of partners show that not all construction service businesses, especially in Banyumas, know and implement BIM. This community service activity is intended to provide basic training to construction service businesses regarding the operation of BIM using Tekla Structures. Method: The method used is a partner needs analysis survey, lectures, demonstrations, discussions, and mentoring. Results: The results of this dedication show that as many as 81% of participants understand the BIM concept after participating in this activity. Conclusion: The holding of this training will provide an overview, improve skills for construction services in Banyumas. Furthermore, it can be applied to the construction process (planning, implementation and maintenance), so that it will produce competitive construction service design products